The Sacred & the Digital. Critical Depictions of Religions in Video Games - Bosman, F.G. (Frank) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Video game studies are a relative young but flourishing academic discipline. But within game studies, however, the perspective of religion and spirituality is rather neglected, both by game scholars and religion scholars. While religion can take different shapes in digital games, ranging from material and referential to reflexive and ritual, it is not necessarily true that game developers depict their in-game religions in a positive, confirming way, but ever so often games approach the topic critically and disavowingly. The religion criticisms found in video games can be categorized as follows: religion as (1) fraud, aimed to manipulate the uneducated, as (2) blind obedience towards an invisible but ultimately non-existing deity/ies, as (3) violence against those who do not share the same set of religious rules, as (4) madness, a deranged alternative for logical reasoning, and as (5) suppression in the hands of the powerful elite to dominate and subdue the masses into submission and obedience. The critical depictions of religion in video games by their developers is the focus of this special issue.